Thermal performance study on coconut husk and kenaf fibre as thermal insulation materials - Nik Abdul Rahman, Nik Kechik Mujahidah; Saadon, Syamimi; Raja Muhammad Azhan Shah, Raja Eizzuddin Shah; Abu Talib, Abd Rahim; Gires, Ezanee; Salleh, Hanim; Abdellatif, Nasser (Semarak Ilmu Publishing, 2024)
Waste heat accounts for 20-50% of industrial energy use, with Southeast Asia processing 40 million tonnes of oil equivalent. Heat losses especially in engines can reduce efficiency, leading to extensive studies to reduce heat loss and improve thermal performance. Heat recovery systems are being studied for recovering lower-grade energy, but not many of them are suitable and economically effective for low temperature waste heat. The objectives of this study are to develop low thermal conductivity agricultural-based material for thermal insulation and investigate the agricultural-based materials' impact on heat transfer rate. The agricultural-based materials that were used in this experiment were coconut husk and kenaf fibre due to their practically low thermal conductivity. The specimens were prepared using two different methods which were needle felting method and fibre-resin blending method. The experiment revealed that coconut husk fibre reinforced with resin (CHER) has the lowest thermal conductivity value of 0.0410 W/m.K and the lowest overall heat transfer rate of 2.85 W, making it an ideal thermal insulation material to be used for low-temperature applications.